MYSTICISM ELEMENTS IN LAW OF BUTON MANUSCRIPT - La Niampe (LITERASI: Indonesian Journal of Humanities, 2011)
This article discusses the mysticism elements (tasawuf) in Undang-undang Buton (Law of Buton) which only function as parable. By using philological approach, I will describe the elements as follow. Firstly, God Element compared to the position of Wolio government, the authority of the Sultan and Sapati. Secondly, the Seven Status Elements compared to seven ranks in Wolio government. Thirdly, the Twenty Characters Elements compared to the total of custom completeness of the Sultan and Sapati. Fourthly, the Al-Qur’an element with thirty-three sections, compared to the total of minister in Wolio government. Fiftly, the Conviction Elements with seventy-two individuals compared to the total of the villages in Wolio government. The existences of the five elements are believed able to give blessing value to Law of Buton. Further, the existence of those elements in Law of Buton also gives political legitimacy for Buton government. Keyword: mysticism elements, Law of Buton, parable, Wolio